Cytotoxic Potential of Silver Nanoparticles - Zhang, Tianlu (Yonsei University College of Medicine, 2014)
Silver nanoparticles (AgNPs) have been widely used in industrial, household, and healthcare-related products due to their excellent antimicrobial activity. With increased exposure of AgNPs to human beings, the risk of safety has attracted much attention from the public and scientists. In review of recent studies, we discuss the potential impact of AgNPs on individuals at the cell level. In detail, we highlight the main effects mediated by AgNPs on the cell, such as cell uptake and intracellular distribution, cytotoxicity, genotoxicity, and immunological responses, as well as some of the major factors that influence these effects in vivo and in vivo, such as dose, time, size, shape, surface chemistry, and cell type. At the end, we summarize the main influences on the cell and indicate the challenges in this field, which may be helpful for assessing the risk of AgNPs in future.